2017
DOI: 10.7575/aiac.alls.v.8n.2p.213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Picture Story Books on Students’ Reading Comprehension

Abstract: As a non formal education students, PKBM (a Non-Formal Community Learning Center) Medaso Kolaka students tend to encounter some difficulties in reading such as low motivation, infrequent tutors (non-formal education teachers) coming, inappropriate teaching materials, etc.  This research aimed to investigate the effects of picture story books on the students’ reading comprehension and to clarify students’ perception on the utilization of  picture story books in teaching reading. The research was conducted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…Furthermore, the estimated marginal means of post-attention span by treatment revealed that pictorial illustration had the highest post-attention span score, followed by music therapy, while the control group had the lowest post-attention span score. The present findings are consistent with the report of Ryu, cited in Roslina (2017), that using dual coding theory (visual and verbal mode) for processing information constitute a challenge, when the system to process the information is more than one. This shows that it is more efficient using two sources of information during classroom activities because it will enhance attention span required for improving comprehension.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…Furthermore, the estimated marginal means of post-attention span by treatment revealed that pictorial illustration had the highest post-attention span score, followed by music therapy, while the control group had the lowest post-attention span score. The present findings are consistent with the report of Ryu, cited in Roslina (2017), that using dual coding theory (visual and verbal mode) for processing information constitute a challenge, when the system to process the information is more than one. This shows that it is more efficient using two sources of information during classroom activities because it will enhance attention span required for improving comprehension.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…Based on the result, the current study's findings are consistent with the findings of earlier investigations. In general, the Pictionary game is a valuable and successful approach for aiding kids in comprehending the reading text ( Halimah et al, 2020;Roslina, 2017;Retno et al, 2021;Stiller & Schworm, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the discussion and analysis results, it is possible to infer that the Numbered Heads Together (NHT) in cooperative learning model supplemented by image puzzle media are beneficial in increasing self-efficacy and student learning outcomes in the coordinate system content. (Roslina: 2017) also sought to explore the impact of image storybooks on students' reading comprehension and explain students' perceptions of using picture storybooks in reading. The findings demonstrated that picture storybooks might increase pupils' reading and their enthusiasm for reading.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, revisi juga dilakukan dengan menambahkan gambar pada latar panduan. Gambar, dalam hal ini, dapat menarik minat dan menumbuhkan motivasi membaca, dan menambahkan kesan ilustratif pada sebuah tulisan (Cao et al, 2018;Roslina, 2017;Villarreal et al, 2015).…”
Section: Pembahasanunclassified